'Market justice' in China and Russia. Issue 3 (3rd July 2018) - Munro, Neil
Abstract: Market justice is an important concept in neoliberal discourses legitimating unequal distribution of welfare within societies. This article explores the question of how useful it is for understanding distributive justice attitudes in Russia and China. It is based on a comparative literature review and an analysis of focus group discussions carried out in most provincial cities in both countries in 2012 and 2013. The literature review shows that Russia is closer to a neoliberal state. China, by contrast, has never followed neoliberal prescriptions, either ideologically or as a matter of practical policy, pursuing instead the goal of a 'socialist market economy'. The focus group discussions show that Chinese tend to view responsibility for welfare as shared between the state and individuals, whereas Russians, depending on their ideology, tend to view welfare as the exclusive responsibility of either the state or the individual. Russians are also more cynical about the way their economy works, suggesting their support for individual responsibility may sometimes shade into social Darwinism.